2003
DOI: 10.1007/s00586-003-0542-y
|View full text |Cite
|
Sign up to set email alerts
|

Back pain remains a common symptom in old age. A population-based study of 4486 Danish twins aged 70?102

Abstract: Introduction A recent survey of over 100,000 Medicare beneficiaries aged 65 and older showed that heart and lung disease and back pain (BP) were the most important factors affecting the average physical health status of older Americans [6]. Yet out of the total body of publications on BP, surprisingly little research has focused on BP in old age, and there is an under-representation of the older population in the BP literature [3]. Furthermore, the authors of the most extensive review so far dealing with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
1
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 31 publications
1
89
1
11
Order By: Relevance
“…The use of this instrument has, however, not become widespread, partly due to the fact that it is only available in English and most studies continue to use their own definition of LBP and their own questionnaires. The use of point prevalence [16], 4-week prevalence [1], and one-year prevalence [2] in different studies further imposes difficulties for comparisons. It is possible that the 12-month recall period we use is associated with recall bias, perhaps avoidable by a shorter period and the use of 4-week prevalence [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of this instrument has, however, not become widespread, partly due to the fact that it is only available in English and most studies continue to use their own definition of LBP and their own questionnaires. The use of point prevalence [16], 4-week prevalence [1], and one-year prevalence [2] in different studies further imposes difficulties for comparisons. It is possible that the 12-month recall period we use is associated with recall bias, perhaps avoidable by a shorter period and the use of 4-week prevalence [16].…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain (LBP) is one of the most common musculoskeletal disorders [1][2][3]. A recent review infers the prevalence of LBP to be highest in middle-aged adults and in women [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers found that the prevalence of pain in various body regions declines with age; however, the degree of pain interference with daily life increases with age (Thomas et al, 2004). Chronic low back pain (CLBP) is one of the most disabling and therapeutically challenging pain conditions afflicting older adults yet there is a limited body of research dedicated to defining its impact on function (Hartvigsen et al, 2003). In contrast, there has been extensive research conducted on workingaged adults with CLBP in part due to the costs associated with work-related disability.…”
Section: Introductionmentioning
confidence: 99%
“…Uma pesquisa longitudinal com gêmeos desenvolvida na Dinamarca entre os anos de 1995 e 2001 revelou que dores nas costas estavam associadas à extensa lista de comorbidades, tanto em análise univariada como na análise multivariada. As mais destacadas foram as doenças musculoesqueléticas, entretanto, cefaleia, doenças respiratórias, cardiovasculares e a úlcera gástrica também foram significantemente associadas às dores nas costas 39 . Comparados com a população normal de referência, pacientes com lombalgia apresentaram mais dorsalgia, cervicalgia, dores em membros inferiores ao realizar exercícios, cefaleia, enxaqueca, problemas para dormir, ondas de calor, ansiedade, tristeza e depressão em pesquisa conduzida na Noruega 40 .…”
Section: Discussionunclassified